Peer Review Journal of Integrated Research Articles: The Impact of Trust and Perception of Type II Diabetes Mellitus Patients on Disease Control Compliance and Nutritional Status of Adolescents in the Family Environment. - Antonio Ximenes; Joaquin Pinto; Sancha Liliana Maria dos Santos; Isabel Barotolumeu Freitas; Remígia Auxiliadora de Jesus Ximenes; Saturnina Julieta Geri de Sena Amaral (Universitas STRADA Indonesia, 2025)
This study comprehensively examines the relationship between various aspects of beliefs and perceptions of Type II Diabetes Mellitus (T2DM) patients on disease control adherence, as well as its impact on adolescents' nutritional status and dietary patterns within the family environment. The analysis was conducted on 5 research journal titles covering factors such as trust in healthcare professionals, insulin therapy, oral medications, social support, health education, as well as perceptions of complication risks, quality of life, stigma, treatment costs, and family roles. The aim of this integrated study was to identify key variables influencing T2DM patients' self-care behaviors and their implications for adolescent nutritional health, as well as to provide recommendations for more effective interventions. The review results indicate that beliefs and perceptions play a crucial role in shaping patient adherence, which ultimately influences adolescents' nutritional environment and health status.